Analyzing latent categories of stress, anxiety, and depression in medical students: insights into their psychological resilience - Lei, Huang; Jiaming, Jiang; Bin, Huang; Lyu, Yuwen; Junrong, Liu; Lam, Lawrence T.; Yufei, Chen (Frontiers in Psychology, 2025)
ObjectiveTo explore the potential effects of demographic variables and three factors of psychological resilience, tenacity, strength, and optimism on the stress, anxiety, and depression of medical students, and to provide data support for the refinement of mental health interventions.MethodA total of 1,099 junior medical students were selected from a certain medical college and surveyed using the Depression Anxiety Stress Scale (DASS-21 Chinese version) and the Connor–Davidson Resilience Scale(CD-RISC Chinese version), as well as a self-designed demographic questionnaire. Data processing was conducted using latent category analysis, contingency table analysis, logistic regression, and other methods.ResultThree subgroups for stress and depression, and two subgroups for anxiety were obtained. Contingency table analysis results showed that the correlation coefficients between the subgroups and severity were all greater than 0.6. In normal and mild symptomatic populations, latent category analysis fitted the low stress subgroup and the depression subgroup with insufficient motivation. The logistic regression results showed that psychological resilience factors had different effects on the latent categories of stress, anxiety, and depression. Optimism only had a significant predictive effect on the latent category of stress, while for the latent category of anxiety, only strength had a significant predictive effect. The disharmonious or average family atmosphere were common high-risk factors for high stress, high anxiety and high depression subgroups. The experience of living on campus in high school was a unique influencing factor of anxiety among medical students. Male gender and low subjective socio-economic status were unique influencing factors for the high depression group, while left-behind experience was a unique influencing factor for the depression group with insufficient motivation.LimitationsThe explanatory power of cross-sectional studies and non-random sampling is limited, and the universality and misrepresentations of the results need further verification.ConclusionThere was significant group heterogeneity in the manifestations of stress, anxiety, and depression among medical students, and the behavioral response patterns of subgroups with latent categories exhibited cross group characteristics when grouped by the norm. The impact of tenacity, strength, and optimism on subgroups of stress, anxiety, and depression varied. Future research should integrate different research paradigms, deepen understanding, and provide more targeted evidence support for psychological education and intervention programs for medical students.